Covid-19 Pandemic, 2020 Financial Performance and Strategy of Panti Waluyo Hospital Surakarta - Kristyanti, Margarita Riyan (Academic Hospital Journal, 2022)
Background: The annual report of Panti Waluyo Hospital Surakarta in 2020 shows deficit by disturbances in cash flow. The financial report is assessed and classified for its performance based on financial ratio analysis in accordance with YAKKUM Performance Indicators. Objective: Measuring the influence of the Covid-19 pandemic on the financial performance rating in 2020 by mapping problems, and establishing a management strategy for the Hospital so that financial performance remains in the Healthy category during the Covid-19 pandemic. Design: This research uses descriptive qualitative research with a case study approach. The data was taken from the financial statements in 2020 and interviews with the Directors. The data is processed by presenting and drawing conclusions. Results: Mapping the problem can effectively measure the effect of the Covid-19 pandemic on the financial performance in 2020. The implemented management strategy was able to stabilize financial performance to remain in the Healthy category. Conclusions: Hospital management must be able to understand the events that occur from the description of the movement of financial accounts, then from these considerations are encouraged to make decisions.